2009
DOI: 10.1111/j.1095-8312.2009.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

An integrative approach to the taxonomy of the pigmented European Pseudomonocelis Meixner, 1943 (Platyhelminthes: Proseriata)

Abstract: Only a few species belonging to the Proseriata (Platyhelminthes) show a parenchymatic pigmentation, which may aid identification. Among these, Pseudomonocelis agilis has a yellowish body and is provided with a reddish-brown girdle in front of the statocyst. The species is known for limited areas of northern Europe and the Mediterranean. The present study was conducted to assess both the taxonomic status of populations attributed to the species across the unusually wide range for an interstitial flatworm, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 51 publications
3
27
0
1
Order By: Relevance
“…This practice has been recently advocated as the best way to overcome potential caveats of species' delimitation methods (Padial et al, 2009;Casu et al, 2009).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…This practice has been recently advocated as the best way to overcome potential caveats of species' delimitation methods (Padial et al, 2009;Casu et al, 2009).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…Molecular studies of marine meiofauna have shown that wide distributions often consist of multiple cryptic species (e.g., Rocha-Olivares et al 2001;Casu and Curini-Galletti 2004;Derycke et al 2008;Casu et al 2009), a pattern seen in many marine organisms, including those with planktonic larvae (Knowlton 2000). In addition, meiofaunal species exhibit phylogeographic breaks-boundaries between intra-specinc lineages-where no obvious barriers to dispersal exist, suggesting restricted gene flow (Derycke et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, individuals may be eroded from the sediment by wave or current action or dispersed with suspended sediment (Palmer 1988) as well as on macroalgae and other substrata (Thiel and Gutow 2005;Derycke et al 2008). Relatively few phylogeographic studies of meiofauna exist (see Todaro et al 1996;von Soosten et al 1998;Rocha-Olivares et al 2001;Westheide et al 2003;Castro-Longoria et al 2003;Casu and Curini-Galletti 2004;Derycke et al 2005Derycke et al , 2007Derycke et al , 2008Derycke et al , 2010Casu et al 2009Casu et al , 2011Andrade et al 2011), and fewer still across the otherwise well-studied southeastern US phylogeographic boundary (Schizas et al 1999(Schizas et al , 2002. As a result, we lack a good general understanding of population differentiation in the environment occupied by these organisms.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Nonetheless, it is likely that most meiofaunal species still await discovery and form cryptic species complexes within geographically restricted areas. [2,[22][23][24][25] Widespread convergence and extreme morphological reduction among meiofaunal species present a massive challenge for accurate phylogenetic reconstruction, because morphological and reproductive evidence on their own can mislead inferences of meiofaunal interrelationships and evolutionary history. [24,25] Molecular phylogenetic approaches provide great potential to circumvent these issues and help avoid the circularity intrinsic to using the same morphological and reproductive characters one is trying to understand.…”
mentioning
confidence: 99%
“…[2,[22][23][24][25] Widespread convergence and extreme morphological reduction among meiofaunal species present a massive challenge for accurate phylogenetic reconstruction, because morphological and reproductive evidence on their own can mislead inferences of meiofaunal interrelationships and evolutionary history. [24,25] Molecular phylogenetic approaches provide great potential to circumvent these issues and help avoid the circularity intrinsic to using the same morphological and reproductive characters one is trying to understand. [26] We anticipate that improved understanding of meiofaunal diversity will provide important insights into (i) the origin and early evolutionary stages of metazoans, (ii) the origins of miniaturization through heterochronic developmental mechanisms, and (iii) the patterns and causes of convergent evolution at both organismal and community levels.…”
mentioning
confidence: 99%